The Characteristics of the Letter of Dād and the Miracle of Al-Qur’an - al-Rasyid, Harun (KnE Social Sciences, 2019)
Since ancient times, Arabic has been an actively used language. Arabic language is also renowned as the language of Al-Qur’an (Muslim’s holy book). However, it is important to notice that the Arabic language used for communication is certainly different from that used in the Qur’an, which is also called the classical Arabic language (qodîmah). This Qur’anic Arabic has various unique characteristics. This paper elaborates some specificities and uniqueness of Arabic letter Dād that no other languages in this world bear similarities. Thus, it cannot be denied if this language is used to represent the verses of the Qur’an. Although some challenges were later found in pronouncing this letter after the Qur’an is read by all Muslims throughout the world. The letter Dād, found in the 15 order of the Hijaiyah alphabet has a very close relation to the uniqueness of the Qur’anic Arabic. In fact, the existence of this letter seems to answer the mystery of why the al-Qur’an was revealed by using clear Arabic (bi lisânin ‘arobiyyin mubînin). This paper will also discuss the characteristics of Dād and its uniqueness which make the proof of the authenticity of the language, which also explains why the language, among all other languages in the world is chosen to be the language of Al-Qur’an. Keywords: Arabic, al-qur’an, Hijaiyah, qodîmah, quranic language